EXPLORING QUINOLINE SCAFOLDS THROUGH INSILICO TECHNIQUE FO THE DRUG DEVELOPMENT - Nemade P. Ajay; Dr. Sandeep C. Atram; Dr. Vikrant P. Wankhade; Dr. Nishan N. Bobade; Dr. Shrikant D. Pande (Asian Journal of Pharmaceutical Research and Development, 2026)
Quinoline and its derivatives exhibit potent pharmacological properties, including antimalarial, antimicrobial, anticancer, and anti-inflammatory activities. This review outlines their chemistry, biosynthesis, and identification—highlighting quinine from Cinchona bark. It discusses therapeutic applications, resistance challenges, and drug design innovations, underscoring quinoline’s pivotal role in modern medicinal chemistry. In this study, ten quinoline analogues were designed using ChemSketch, and evaluated for drug‑likeness using Molinspiration, biological activity via PASS, and pharmacokinetic/toxicity profiles through ADMET‑AI. Molinspiration analysis indicated that most analogues meet Lipinski’s criteria, with QA5 and QA10 showing moderate deviations in lipophilicity. PASS predictions for gluconate 2‑dehydrogenase inhibition identified QA1, QA2, and QA7 as having very high activity (Pa > 0.9), with QA2 being the most potent (Pa = 0.975). ADMET‑AI predicted excellent intestinal absorption and high bioavailability for QA1, QA2, QA7, QA8, and QA10; however, QA4, QA5, and QA6 exhibited lower oral bioavailability. Distribution profiles suggested strong blood–brain barrier penetration and high tissue distribution for QA1, QA2, QA5, QA7, and QA8. Metabolic analysis flagged potential CYP1A2 inhibition for QA1, QA3, QA4, QA5, and QA7. Toxicity concerns were highest for QA5 and QA9 (mutagenicity, hepatotoxicity, carcinogenicity), whereas QA2, QA8, and QA10 demonstrated comparatively safer profiles. Overall, QA2 emerges as the most promising candidate, balanced by high predicted efficacy and favorable ADMET/toxicity.